Reforming medical regulation: a qualitative study of the implementation of medical revalidation in England, using Normalization Process Theory. Issue 1 (January 2020) - Tazzyman, Abigail; Ferguson, Jane; Boyd, Alan; Bryce, Marie; Tredinnick-Rowe, John; Price, Tristan; Walshe, Kieran
Objectives: The introduction of medical revalidation in 2012 has been a controversial and radical change to medical regulation in the UK. It involved changes to the way organizations manage medical performance, and to the relationships between doctors, their employers and the professional regulatory body. In this paper, we explore the implementation of medical revalidation, analysing the change process and its consequences for doctors and organizations. Methods: We conducted a qualitative investigation of the implementation of revalidation in 15 case study organizations in 2016–2017, collecting documents and undertaking a total of 80 interviews with medical and non-medical staff. We used Normalization Process Theory to frame and structure the analysis. Results: Revalidation reforms were largely implemented successfully within and across our case study organizations, with evidence of growing acceptance of the purpose and processes of revalidation. There was an emergent shift from securing doctors' compliance towards the use of revalidation to strengthen clinical governance, and towards evaluating revalidation processes and seeking to make them more effective. However, there was substantial variation in the implementation and impact of revalidation; it was still not fully understood by many doctors, and revalidation processes were highly reliant on a few key individuals in each organization. The changes brought about by revalidation have had consequences for the way in which doctors construct their identity and the way they relate to the organizations in which they work. Conclusion: Despite considerable early scepticism and overt opposition in the medical profession, revalidation has become gradually accepted, embedded and even valued over time. Its impact and effectiveness are still questioned by many stakeholders, and the focus of attention has now shifted towards revising and improving the way revalidation works in practice.